GP frequent consulters: their prevalence, natural history, and contribution to rising workload. - Gill, D; Dawes, M; Sharpe, M; Mayou, R (1998)
A small proportion of patients use a disproportionate amount of general practitioners' (GPs') time. We demonstrate here that such frequent attending behaviour tends to persist through five-year follow-up, suggesting the need for the development of specific management strategies. We also show that, at any rate in one practice, total workload is increasing dramatically, and that frequent consulters make up a large part of the increase.